Towards sustainable rural development: Characteristics and influencing factors of spatial correlation network of China’s rural digitalization development - Xiaolong Gan; Shuang Xiang; HuEr Shuang; Tao Wen (Sustainable Futures, 2025)
This study explored the spatial correlation network of China’s rural digitalization development. The findings indicate that the spatial correlation network exhibited a relatively loose structure with a notable core-periphery characteristic, and can be partitioned into the main inflow block, the main outflow block, the bidirectional spillover block, and the agent block. Technical innovation, human capital, transportation facilities, and industrial structure were identified as substantial influencers of the spatial correlation network. Generally, the siphoning effect outweighs the spillover effect, resulting in significant regional disparities in rural digitalization development. Finally, several suggestions are proposed to foster coordinated rural digitalization development in China.